(untitled) (Bangladesh Journal of Anatomy, 2014)
Context and rationale: The age related infertility due to early ovarian ageing is one of the problems for women who want to become pregnant in late age in our country. Ovarian ageing reflects in its morphology. So this study was aimed at determining the gross morphology of the ovary in different age groups of Bangladeshi female (cadaver) to assess the possible relationships among different morphological variable of ovaries in different age groups. The present study would serve as a baseline data for the gynecologist, obstetricians and endocrinologist about the onset of infertility in the context of Bangladesh. Materials and methods: Cross sectional analytical type of study was conducted at the department of Anatomy, Rangpur Medical College, Rangpur. Fifty pairs postmortem human ovaries from Bangladeshi female aged between 15 and 45 years were examined for morphological study. The morphological parameters such as length, breadth, circumference, weight and volume of the right and left ovaries determined by physical method and the data were compared between different age groups. Result: Mean length, circumference and volume were significantly higher in group A than the other groups in both right and left sides. The difference reached a significant level (P< 0.05) in both ovaries in between and within groups for all mentioned parameter. The mean breadth of right ovary in group B and mean breadth of left ovary in group A were larger than the other groups but was not significant. Conclusion: The values of the morphological measurements fall from younger to older women. This may be due to depletion of the ovarian non-growing follicles thus reflecting fall in the ovarian reserve. DOI: http://dx.doi.org/10.3329/bja.v11i2.20675 Bangladesh Journal of Anatomy, July 2013, Vol. 11 No. 2 pp 77-80